Monitoring of Objects Urban Gardening. Information System «Quality Management of Urban Sites Greening». Issue 4 (1st February 2022) - Avdeeva, E; Ivanov, D; Markelova, K
Abstract: Monitoring of landscaping objects is a system of operational control over the violation of their stability, damage by pests, damage to diseases and other natural and anthropogenic factors of the environment, as well as a system for tracking the dynamics of these processes, which provides early detection of the unfavorable state of plantings, assessment and forecast of the development of ecologically unfavorable situations, obtaining reliable information about undesirable changes in nature under the influence of anthropogenic impact and materials for substantiating and making timely decisions. The article presents an algorithm for the formation of the information and analytical system "Quality management of urban landscaping objects". At the first stage in the monitoring process, the tasks of observation and data acquisition are solved, such as: substantiation of the number and location of permanent observation sites in the city plan, which should be maximally represented in all zones of the city and in all categories of green areas; thematic mapping; creation of an information model. Approbation of the formation of a passport for the planting object of these techniques is presented on the example of a park in Krasnoyarsk.